Core-Shell Structure of Intermediate Precipitates in a Nb-Based Z-Phase Strengthened 12% Cr Steel. (20th March 2017) - Rashidi, Masoud; Andrén, Hans-Olof; Liu, Fang
Abstract: In creep resistant Z-phase strengthened 12% Cr steels, MX (M=Nb, Ta, or V, and X=C and/or N) to Z-phase (CrMN, M=Ta, Nb, or V) transformation plays an important role in achieving a fine distribution of Z-phase precipitates for creep strengthening. Atom probe tomography was employed to investigate the phase transformation in a Nb-based Z-phase strengthened trial steel. Using iso-concentration surfaces with different concentration values, and subtracting the matrix contribution enabled us to reveal the core-shell structure of the transient precipitates between MX and Z-phase. It was shown that Z-phase forms by diffusion of Cr into NbN upon ageing, and Z-phase has a composition corresponding to Cr1+ x Nb1− x N with x =0.08.